Serious about Change: A Gendered Examination of the Impact of Offense Type on Parole Success. Issue 5 (19th October 2016) - Blackburn, Ashley G.; Pfeffer, Rebecca D.; Harris, Judith A.
Abstract : Female offender populations are growing at an unprecedented rate. The present study examines gender differences among a large sample of male and female offenders as related to seriousness of their offense and success on parole. Data analyzed were originally collected from a random sample of parole case files in California. Results revealed that although gender does significantly impact parole success, seriousness of the offense does not. Other significant factors include age at release on parole, criminal history, and measures of stability upon release. The need for wrap-around services, comprehensive treatment models, and funding for gender-specific services are discussed.